2019
DOI: 10.1002/adsc.201801569
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Enantioselective Hydroaminations for Production of N‐Cycloalkyl‐Substituted L‐Aspartic Acids Using Two C−N Lyases

Abstract: N-cycloalkyl-substituted amino acids have wide-ranging applications in pharma-and nutraceutical fields. Here we report the asymmetric synthesis of various N-cycloalkyl-substituted laspartic acids using ethylenediamine-N,N'-disuccinic acid lyase (EDDS lyase) and a previously engineered variant of methylaspartate ammonia lyase (MAL-Q73A) as biocatalysts. Particularly, EDDS lyase shows broad non-natural substrate promiscuity and excellent enantioselectivity, allowing the selective addition of homo-and heterocyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Recently, we reported that ethylenediamine-N,N 0 -disuccinic acid (EDDS) lyase naturally catalyzes a reversible two-step sequential addition of ethylenediamine (2) to two molecules of fumaric acid (3), giving (S)-N-(2-aminoethyl)aspartic acid (AEAA, 4) as an intermediate and (S,S)-EDDS (5) as the final product (Table 1A). 12 EDDS lyase was subsequently found to have broad substrate promiscuity, [13][14][15] accepting a wide range of amino acids with terminal amino groups (6a-k) for regio-and stereoselective addition to fumarate, thus providing a straightforward biocatalytic method for the asymmetric synthesis of AMA (1a), AMB (1b), and related aminocarboxylic acids (1c-k, Table 1B). 13 To further explore the substrate scope of EDDS lyase, as well as to prepare a small library of EDDS derivatives as potential NDM-1 inhibitors, 16 we here describe the EDDS-lyase catalyzed reaction of fumaric acid with various diamines containing different aliphatic linkers between the two amino functional groups (7a-i) ( Table 2).…”
mentioning
confidence: 99%
“…Recently, we reported that ethylenediamine-N,N 0 -disuccinic acid (EDDS) lyase naturally catalyzes a reversible two-step sequential addition of ethylenediamine (2) to two molecules of fumaric acid (3), giving (S)-N-(2-aminoethyl)aspartic acid (AEAA, 4) as an intermediate and (S,S)-EDDS (5) as the final product (Table 1A). 12 EDDS lyase was subsequently found to have broad substrate promiscuity, [13][14][15] accepting a wide range of amino acids with terminal amino groups (6a-k) for regio-and stereoselective addition to fumarate, thus providing a straightforward biocatalytic method for the asymmetric synthesis of AMA (1a), AMB (1b), and related aminocarboxylic acids (1c-k, Table 1B). 13 To further explore the substrate scope of EDDS lyase, as well as to prepare a small library of EDDS derivatives as potential NDM-1 inhibitors, 16 we here describe the EDDS-lyase catalyzed reaction of fumaric acid with various diamines containing different aliphatic linkers between the two amino functional groups (7a-i) ( Table 2).…”
mentioning
confidence: 99%
“…We continued our investigations by testing whether EDDS lyase, which has previously been shown to possess an exceptionally broad amine scope, [18][19][20] can accept 2 a as an unnatural substrate in the hydroamination of 1. Pleasingly, EDDS lyase accepted 2 a for addition to 1, giving rise to 3 a.…”
Section: Resultsmentioning
confidence: 99%
“…Here we report the engineering of an effective C-N lyase, based on ethylenediamine-N,N'-disuccinic acid (EDDS) lyase from Chelativorans sp. BNC1, [18][19][20] for the enantioselective syntheses of l-3 a and l-3 f, precursors to neotame and advantame, respectively, as well as related chiral synthons for aspartame-based sweeteners starting from the simple nonchiral compound fumaric acid (1, Scheme 1 C). This newly engineered C-N lyase shows a 1140-fold increase in activity for the selective hydroamination of fumarate compared to that of the wild-type enzyme, opening up new opportunities to design practical multienzymatic processes for the more sustainable and step-economic synthesis of an important class of food additives.…”
Section: Introductionmentioning
confidence: 99%
“…Her current research interests include exploring the reactivity of enzymes from natural product biosynthesis pathways for producing pharmaceutically relevant molecules. [16][17][18][19][20][21] Ph, aryl H H RgPAL, AvPAL, PcPAL phenylalanine, β-aryl α-alanines [6,[22][23][24][25][26] chelating compound widely used in industry for a wide range of applications, such as soil remediation, paper manufacturing, waste water treatment and so on. (S,S)-EDDS was isolated as a secondary metabolite from the actinomycete Amycolatopsis japonicum, hypothetically serving as a scavenger of zinc (zincophore) and its bioproduction was strictly repressed by zinc.…”
Section: Properties Structure and Catalytic Mechanismmentioning
confidence: 99%
“…BNC1 was also employed for enantioselective synthesis of complex N-cycloalkyl substituted l-aspartic acids, which are structurally distinct from its natural substrates ( Figure 5). [17] Reactions were performed with fumaric acid, various homo-and heterocycloalkyl amines (comprising four-, five-and six-membered rings) and EDDS lyase at pH 8.5 and room temperature. EDDS lyase exhibited broad substrate promiscuity, accepting a variety of cycloalkylamines in hydroamination of fumarate to give the corresponding N-cycloalkyl-l-aspartic acids with excellent enantioselectivity (ee > 99 %).…”
Section: Synthetic Applicationsmentioning
confidence: 99%